2020
DOI: 10.1177/1354816620949722
|View full text |Cite
|
Sign up to set email alerts
|

Option framing for upselling tourism services: Does cognitive availability prevent irrational choices?

Abstract: This article examines the effect of option framing and cognitive load on consumer choices of tourism services. Previous literature has shown that consumers tend to choose more options and spend more money when they begin the choice process from a complete set of options (downgrade/delete framing) than when they start choosing from a more basic set of options (upgrade/add framing). To exam this irrational behavior, we conducted two experimental studies with 561 consumers of leisure travel. The results of the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
(115 reference statements)
0
9
0
Order By: Relevance
“…Push management is to preprocess and classify this redundant and wrong tourism information first, retain useful tourism information, and eliminate interference information [ 22 , 23 ]; through the classified retrieval of customized tourism information for tourists, the most economical tourism information transmission mode is selected in the Internet of things environment, the tourism information categories required by tourists are generated, and directional and regular push is realized [ 24 ]. The tourism information push module has a two-way information interaction function; that is, on the one hand, it transmits basic tourism information to tourists, and on the other hand, it also receives tourists' feedback, to optimize each module of the system and continuously improve the database [ 25 ]. Database Module .…”
Section: Realize the Design Of Intelligent Tourism Information Servic...mentioning
confidence: 99%
“…Push management is to preprocess and classify this redundant and wrong tourism information first, retain useful tourism information, and eliminate interference information [ 22 , 23 ]; through the classified retrieval of customized tourism information for tourists, the most economical tourism information transmission mode is selected in the Internet of things environment, the tourism information categories required by tourists are generated, and directional and regular push is realized [ 24 ]. The tourism information push module has a two-way information interaction function; that is, on the one hand, it transmits basic tourism information to tourists, and on the other hand, it also receives tourists' feedback, to optimize each module of the system and continuously improve the database [ 25 ]. Database Module .…”
Section: Realize the Design Of Intelligent Tourism Information Servic...mentioning
confidence: 99%
“…There have been several studies on understanding customer satisfaction based on service quality (Nicolini & Salini, 2006;Zins, 2001;Eti & Mızrak, 2020). However, these works do not explicitly consider the problem of upselling (Mayer et al, 2020), which is a notable gap in the research given the importance of upselling to businesses in the travel sector (Denizci Guillet, 2020). Ostrowski et al (1993) showed that sufficient investment in excellent service quality influences the raises in customer loyalty in the long-term, positively impacting the revenue; however, the study was based mainly on surveys of U.S. airline travelers in 35 different U.S. airports.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results generally showed a promising approach to raise 'customers' willingness to purchase upselling products and increase network 'operators' revenue. Mayer et al (2020) analyzed the impact of option framing and cognitive load on tourism 'services' customer choices. Irrational behavior has been noticed in that customers consume more when choosing downgrade than when they upgrade.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mayer et al (2022) presents a collaboration between Universidade Federal Fluminense and University of Sao Paulo in Brazil. The paper, grounded in behavioural economics, challenges consumers’ behaviour rationality by examining two experimental studies with 561 leisure travellers.…”
mentioning
confidence: 99%
“…In terms of contributions, the paper provides statistics for multidimensional spatial data, and her results provide elements necessary for appropriately defining local development strategies. Mayer et al (2022) presents a collaboration between Universidade Federal Fluminense and University of Sao Paulo in Brazil. The paper, grounded in behavioural economics, challenges consumers' behaviour rationality by examining two experimental studies with 561 leisure travellers.…”
mentioning
confidence: 99%